Північноприазовська пізньопалеолітична культура - Оленковський, М.П. (Археологія, 2001)
Обґрунтовано виділення нової пізньопалеолітичної культури на півдні України. Розглянуто її походження, культурно-історичний розвиток, періодизацію та хронологію. Подано опис пам’яток цієї культури та проаналізовано археологічний матеріал. Статья посвящена новой позднепалеолитической культуре юга Украины, выделенной автором. Многократное увеличение в последние два десятилетия количества открытых и исследованных раскопками памятников позднего палеолита в данном регионе позволяет провести культурно-историческую структуризацию. В выделенную культуру включены памятники Капустяна балка, Сомова балка, Федоровка (оба слоя), Каштаева балка, Солонэ озеро IX, Солонэ озеро IХа, Велывальская балка, Лысая гора, Канцерка II. Сделан вывод о том, что культурную подоснову североприазовской культуры представляет каменнобалковская культура, локализованная в регионе Нижнего Дона. Аргументирован достаточно поздний возраст выделенной культуры в рамках заключительной поры позднего палеолита. Автор считает показательной близость пути развития индустрий каменнобалковской — североприазовской культур и имеретинской культуры Закавказья. The article is devoted to a new Late Palaeolithic culture in the south of Ukraine, separated by the author. The multiple increments of the quantity of sites of the Late Palaeolithic age, which are open and investigated by excavations in this region, allow us to carry out the cultural and historical structurization. The separated culture includes such sites as the gullies of Kapustyana and Somova, Fedorivka (both layers), the Kashtaeva gully, the Solone IX lake, the Solone IXa lake, the Velyvalska gully, the Lysaya mount, and Kantserka II. An unambiguous conclusion is drawn about such a fact that the cultural underlying base of the culture of the Northern Azov Sea region is the culture of the Kam’yana gully, which is localized in the Lower Don River region. The sufficiently late age of the separated culture within the final stage of the Late Palaeolithic age is argued. The author considers the closeness of the ways of development of industries in the cultures of the Kam’yana gully and the Northern Azov Sea region and the Imeretian culture of the Transcaucasian region as significant.